2010
DOI: 10.1177/0269216310368578
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the development of palliative care in Western Europe

Abstract: substantially from each other in both their scope and context and that some may be considered to be of greater significance than others. A number of common barriers to the development of the discipline do exist and much work still remains to be done in the identified areas. This paper provides a road map of which barriers need to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 5 publications
3
44
0
3
Order By: Relevance
“…A number of common themes have emerged from these studies, including (1) a lack of awareness of palliative care as a field, and inadequate understanding of palliative care needs at a public and governmental level; (2) limited fi nancial and material resources; (3) inadequate professional training programs; and (4) problems relating to opioid availability. [14][15][16][17][18][19] This study has limitations. First, the proportion of individuals responding to our survey was low.…”
Section: Discussionmentioning
confidence: 96%
“…A number of common themes have emerged from these studies, including (1) a lack of awareness of palliative care as a field, and inadequate understanding of palliative care needs at a public and governmental level; (2) limited fi nancial and material resources; (3) inadequate professional training programs; and (4) problems relating to opioid availability. [14][15][16][17][18][19] This study has limitations. First, the proportion of individuals responding to our survey was low.…”
Section: Discussionmentioning
confidence: 96%
“…Research is often associated with training, particularly postgraduate education. This issue is of such importance that the opportunity deficits in education and training are often cited as barriers to the development of palliative care in Western Europe (10)(11) . In Portugal, the offer of training in this area has been increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we conducted the content analysis 9 with support of the software MAXQDA 11 (version 11, VERBI Software-Consult-Sozialforschung GmbH, Berlin, Germany). 10 Two of the coauthors (LDL and TP) identified common issues, and inductive categories were created and discussed until an agreement was achieved.…”
Section: Methodsmentioning
confidence: 99%